A whole-genome sequence study identifies genetic risk factors for neuromyelitis optica - Karol Estrada (Nature Portfolio, 2018)
Neuromyelitis optica (NMO) is a rare autoimmune condition characterized by inflammation and demyelination of the optic nerve and the spinal cord. Here, Estrada et al. identify NMO susceptibility variants in the MHC region and find that autoantibody-positive NMO genetically overlaps with lupus.